CLASSIFYING SENTENCES BY THEIR PURPOSE IN COMMUNICATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the four primary sentence types—declarative, interrogative, imperative, and exclamatory—based on their purpose of expression. It explains the function of each sentence type in communication, highlighting how declarative sentences inform, interrogative sentences seek information, imperative sentences issue commands or requests, and exclamatory sentences express strong emotions. The article also provides practical examples for each type, emphasizing the importance of understanding and using sentence forms effectively for clearer and more dynamic communication. The conclusion reinforces how mastering these sentence types enhances interpersonal interactions and ensures more effective expression of ideas and emotions. This article provides a detailed examination of sentence types categorized by their intended purpose: declarative, interrogative, imperative, and exclamatory. Each type is explained in terms of its function—conveying information, asking questions, giving commands, or expressing emotions—along with examples that illustrate their practical use. By breaking down the key differences and applications of these sentence types, the article emphasizes how their strategic use can improve communication. Additionally, it underscores the significance of understanding the nuances of sentence forms to adapt language effectively to different contexts, fostering clearer, more impactful conversations. The article offers a foundation for both beginners and advanced learners looking to refine their communication skills in both written and spoken forms.